Indoor climate experience, migration, and thermal comfort expectation in buildings. (15th August 2018) - Luo, Maohui; Wang, Zhe; Brager, Gail; Cao, Bin; Zhu, Yingxin
Abstract: Advances in heating, ventilation and air conditioning (HVAC) technologies have dramatically improved the indoor thermal environment, but attention should be paid on how this would affect building occupants' thermal comfort perception. In this paper, we studied the mutually dependent relationship between indoor climate experience and occupants' comfort expectation. An intriguing experiment was conducted in China where wintertime indoor thermal environments in northern cities (with district heating) are much warmer than in southern region (without district heating). By analyzing the 4411 responses from four college-aged subject groups with different indoor thermal history, two interesting findings emerged. Firstly, people's understandings of thermal comfort change with their indoor thermal experiences. Those permanently live in lower-grade non-neutral thermal environment can achieve similar thermal comfort perception as those who live in long-term comfortable thermal conditions. Secondly, the dynamics of building occupants' thermal comfort adaptation project asymmetric trajectories. It is much quicker for occupants to accept neutral indoor climate than to lower their expectation and adapt to under-conditioned environments. These two phenomena can be well described by the index "demand factor", which can serve as a reference for future thermal comfort study. Graphical abstract: Image 1 Highlights: This study explores indoor climate experience and thermal comfort expectation. 4411 responses from subject groups with different indoor thermal history were collected. The results show that people's understandings of thermal comfort are malleable. The dynamics of building thermal comfort adaptation exhibit asymmetric trajectories. The index "demand factor" was adopted to describe expectation dynamics.